1996
DOI: 10.1172/jci118707
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin and cytokines decrease serum levels and extra hepatic protein and mRNA levels of cholesteryl ester transfer protein in syrian hamsters.

Abstract: Endotoxin alters the metabolism of lipoproteins, including that of high density lipoprotein (HDL). Cholesteryl ester transfer protein (CETP) facilitates exchange of HDL cholesterol for very low density lipoprotein (VLDL) triglyceride, leading to catabolism of HDL. We investigated the effects of endotoxin and cytokines on CETP in Syrian hamsters. Endotoxin induced a rapid and progressive decrease in serum CETP levels; by 48 h CETP had decreased to Ͻ 20% of control levels. Endotoxin also decreased CETP mRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 49 publications
(32 reference statements)
2
48
0
3
Order By: Relevance
“…Notable among the dimorphically induced genes was a TNF␣-induced protein, suggesting a possible differential effect of TNF␣ on target genes. Hepatic TNF␣ is induced by the bile acid-enriched diet, and both CETP and Cyp7a are repressed by TNF␣ (32)(33)(34). DISCUSSION We have shown that the orphan nuclear receptor LRH-1 binds and transactivates the human CETP promoter.…”
Section: Regulation Of Cetp Gene By Bile Salt In Cetp Transgenicmentioning
confidence: 82%
See 1 more Smart Citation
“…Notable among the dimorphically induced genes was a TNF␣-induced protein, suggesting a possible differential effect of TNF␣ on target genes. Hepatic TNF␣ is induced by the bile acid-enriched diet, and both CETP and Cyp7a are repressed by TNF␣ (32)(33)(34). DISCUSSION We have shown that the orphan nuclear receptor LRH-1 binds and transactivates the human CETP promoter.…”
Section: Regulation Of Cetp Gene By Bile Salt In Cetp Transgenicmentioning
confidence: 82%
“…Thus, the TNF␣-induced protein 2 was increased in males and decreased in females, suggesting that there could be a dimorphic effect of TNF␣ signaling in male versus female mice. Hepatic TNF␣ expression is induced by the cholic acid diet (it is probably made in Kupffer cells) (33), and TNF␣ has been shown to repress both CETP (34) and Cyp7a (32). If the effect of TNF␣ is larger in male mice, this could explain why CETP is repressed in this sex.…”
Section: Regulation Of Cetp Gene By Bile Salt In Cetp Transgenicmentioning
confidence: 99%
“…Furthermore, TNF-a reduced the levels of mRNA for CETP in muscle, heart, intestine, stomach, and kidney, but not in adipose tissue while IL-1 was administered together they were much more effective than the individual cytokines and decreased CETP mRNA expression in all the tissues. 80 Injection of TNF to cynomolgus monkeys decreased plasma LCAT activity, plasma cholesterol level, and decreased content of cholesterol ester in LDL and HDL particles. 81 In HepG2 cells, rH-TNF-a dose dependently decreased the concentrations of apolipoprotein (apo) A-I, apoB, and LCAT activity in the medium after 24 h of incubation.…”
Section: Effects Of Tnf-a On Cholesterol Metabolismmentioning
confidence: 98%
“…For example, a decrease in PPAR␣ may contribute to the reduced expression of acyl-CoA synthetase (29,34) and carnitine palmitoyltransferase I (45) during the APR. Similarly, a decrease in LXR, LRH, and SHP may contribute to the decrease in cholesteryl ester transfer protein (46). Because many of the proteins regulated by nuclear hormone receptors are involved in the metabolism of triglycer- 5 Hep3B cells were plated in 100-mm Petri dishes in culture media containing 10% serum.…”
Section: Fig 2 Effect Of Lps Treatment On Binding Of Hepatic Nuclearmentioning
confidence: 99%